Manufacturing Flexibility and Agility: A Distinctive Comparison - Ali, A.; Jahanzaib, M.; Aziz, H. (The Nucleus, 2014)
Both flexibility and agility are requisite for the successful operation of organization. From manufacturing perspective, there is still confusion of using, implementing and understanding of both concepts. This paper addresses the issue of both in a coherent manner and examined the comparison from manufacturing point of view. It has been learnt that there is a difference of „engineer to order‟ and „innovate to order‟, responsiveness, business network and level of organizational resources. This has been concluded with similarity and differences and stated that forecasting and adaptability are similar key indicators.